GEOLOGY, MINERALOGY AND ORIGIN OF CLAY MINERALS OF THE PLIOCENE FLUVIAL-LACUSTRINE DEPOSITS IN THE CAPPADOCIAN VOLCANIC PROVINCE, CENTRAL ANATOLIA, TURKEY - Gürel A.; Kadır S. (My University, 2006)
The Güzelöz-İncesu Plateaus are situated in the central and eastern parts of the Cappadocian volcanic province (central Anatolia). This province contains many ignimbrite levels, andesite, basalt intercalated with several paleosols, calcrete, carbonate, fluvial sediments, diatomaceous clayey sediments and pyroclastic sedimentary levels. The presence of mottling, sesquioxide, root traces, rhizoids and burrows in continuous, finely bedded and laminated sediments, paleosols, calcrete, the occurrence of bone- and teeth-bearing reworked pyroclastic materials, and the description of the lithofacies in the study area indicate fluvial and shallow-lake environments. These environments are dominated by smectite and illite, with traces of kaolinite, associated mainly with plagioclase, K-feldspar, quartz, calcite, opal-CT, pyroxene (diopside, rare hypersthene), and locally trace amounts of gypsum and sepiolite. Smectite predominates in paleosols and calcrete units, and generally increases upwards in the profiles, coinciding with a gradual increase in the degree of alteration. Partial to complete alteration of plagioclase, K-feldspar, pyroxene and partial devitrification of glass-shard particles in pyroclastic rocks, development of microsparitic to sparitic cement comprising euhedral rhombic calcite crystals between irregular clay nodules in paleosol and calcrete samples, along with the occurrence of dogtooth-type sparitic crystals in fractures, desiccation cracks and geopetal-type fenestrae, indicate alternating periods of drought and wet, resulting in the development of paleosols and calcretes. Micromorphological development of spongiform smectite on mainly relict feldspar and, locally, on glass shards, indicates an authigenic origin, whereas illite formed either authigenically or by conversion of smectite to illite-smectite.
Keywords: CALCRETE; CAPPADOCIAN VOLCANIC PROVINCE; CENTRAL ANATOLIA; CLAY MINERALS; PALEOENVIRONMENT; PALEOSOL; TURKEY; Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен